Contemporary U. S. Tax Policy - Steuerle, C. Eugene, (Rowman & Littlefield Publishers, 2008)
C. Eugene Steuerle, one of the country's most influential economists, offers an insider's look at tax policy based on a quarter century of working with officials of all political stripes. Steuerle outlines the principles of taxation and the early postwar period before proceeding to the tax policy battles that began with the Reagan revolution and continue today. Those expecting a simple story of triumph and defeat may be surprised. Rather than moving toward consensus and progress, tax policy history has been messy, repetitive, and often rancorous. Yet evolution-and even revolution-do occur. The second edition has been updated with a look at tax policy during the George W. Bush presidency.